2013
DOI: 10.1111/trf.12157
|View full text |Cite
|
Sign up to set email alerts
|

Lenograstim compared to filgrastim for the mobilization of hematopoietic stem cells in healthy donors

Abstract: In conclusion, the current retrospective study shows that lenograstim and filgrastim are similar in terms of efficacy for the mobilization of hematopoietic stem cells in healthy donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Both lenograstim, a glycosylated form and filgrastim, a nonglycosylated form of G‐CSF, have been used for stem cell mobilization. Recent data support the similar efficacy of these two agents in healthy donors . It has been reported that both of these agents can achieve effective stem cell mobilization yield after chemotherapy.…”
Section: When and How In Daily Practice?mentioning
confidence: 72%
“…Both lenograstim, a glycosylated form and filgrastim, a nonglycosylated form of G‐CSF, have been used for stem cell mobilization. Recent data support the similar efficacy of these two agents in healthy donors . It has been reported that both of these agents can achieve effective stem cell mobilization yield after chemotherapy.…”
Section: When and How In Daily Practice?mentioning
confidence: 72%
“…The recommended dose is 10 mg/kg body weight/day, either as a single or split dose. Several studies have demonstrated the superiority of G-CSF as a single agent compared with granulocyte macrophage (GM)-CSF (sargramostim) or combination growth factor support [3][4][5][6][7][8][9][10][11][12][13][14][15]. Equivalent split dosing (5 mg/kg twice daily) or higher split dosing (12 mg/kg twice daily) has been reported to result in higher collection yields with shorter collection times; however, the toxicities of bone pain, fatigue, and headaches were more frequent, and costs were higher [7][8][9][10].…”
Section: Allogeneic Progenitor Cell Transplantmentioning
confidence: 99%
“…Filgrastim (nonglycosylated G-CSF), which is most commonly used in the United States, has been compared with lenograstim (glycosylated G-CSF), which is widely used in Europe, with similar reported outcomes [14,15]. Although the longer acting pegylated G-CSF (pegfilgrastim) is effective, little data support its use given the possibly increased toxicities and higher costs [16,17].…”
Section: Allogeneic Progenitor Cell Transplantmentioning
confidence: 99%